Detecting Gaps in Language Resources and Tools in the Project CESAR - Tadić, Marko (Array, 2014)
In this paper the first preliminary results of the analysis of marks collected within the tables of META-NET series of Language White Papers of CESAR project languages are demonstrated. Although they are preliminary results, we can consider them useful for showing us where real gaps in language resources and tools can be detected.